SOME FEATURES OF PEDIATRIC DISCOURSE - Makhpieva Guldonakhon Kabiljanovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The conducted analysis showed some differences between the pediatrician's discourse and the discourse of an "adult" doctor, namely: the use of diminutive suffixes, gestures, and game techniques. Based on the study of conversation scripts, the features of pediatric discourse were established, including personalization and dialogicity. It was revealed that a pediatrician must have developed lexical skills and speech abilities, verbal thinking, and be able to use communication tactics and strategies to establish and maintain contacts with a child and his parents.